Impact of Cupping Therapy on Blood Pressure in Hypertension Patients at Griya Bekam Az-Zahra - Firmanda, Luthfi; Subekti, Reni Tri; Budianto, Apri; Lestari, Arena (The Indonesian Institute of Science and Technology Research, 2025)
Hypertension is a major global health issue, with its prevalence rising annually. It is estimated that by 2025, 1.5 billion people worldwide will suffer from hypertension, and each year, 9.4 million deaths are attributed to hypertension and its complications. The aim of this study was to assess the effect of cupping therapy on blood pressure in hypertension patients at Griya Bekam Az-Zahra in 2024. This quantitative research employed a quasi-experimental design using a one-group pre-test post-test approach. A sample of 20 respondents was selected through accidental sampling at Griya Bekam Az-Zahra. Data were collected via observation sheets, cupping therapy sessions, and blood pressure measurements. Bivariate analysis was conducted using the Wilcoxon test (α = 0.05). The study took place from June 27 to July 4, 2024. Results showed a significant reduction in both systolic and diastolic blood pressure following cupping therapy. The mean systolic blood pressure decreased from 143 mmHg to 122.5 mmHg, and the mean diastolic pressure dropped from 89.5 mmHg to 78.5 mmHg. Wilcoxon test results indicated that wet cupping therapy significantly affects blood pressure, with p-values of 0.000 (<0.05) for both systolic and diastolic pressures. In conclusion, wet cupping therapy can positively influence blood pressure in hypertensive patients. This finding suggests that cupping therapy could be a valuable consideration for holistic nursing interventions, incorporating bio-psycho-social-spiritual care for the community, particularly as a complementary nursing treatment.